Breastfeeding Guidance for Orthodox Jewish Families When Newborns Require Special Care and Continued Hospitalization. Issue 2 (March 2019) - Candelaria, Laura M.; Bressler, Toby; Spatz, Diane L.
Abstract : Abstract: There is a growing Orthodox Jewish population in the United States and Canada. Many Orthodox Jewish families have a large number of children and choose to breastfeed. The Orthodox Jew observes Jewish laws and customs literally as dictated by the Torah . Orthodox Jews consult a rabbi or posek before making most major life decisions, including matters related to breastfeeding to ensure adherence to religious law. Cultural practices applicable to the Orthodox Jewish family related to the provision of human milk and breastfeeding when a sick newborn may require special care and continued hospitalization after the mother has been discharged are presented. Guidelines for preconception lactation counseling for families are provided to tailor nursing care to meet the individual needs of each Orthodox Jewish infant and family. Special considerations related to pumping schedule, use of mechanisms such as timers for breast pumps, and discussions with religious leader about the saving of colostrum and/or milk when an infant is critically ill will be addressed. To provide culturally sensitive and appropriate counseling related to the provision of human milk and breastfeeding, nurses need to be culturally aware of the specific needs of the Orthodox Jewish family. Clinical implications and suggestions are provided. Abstract : Cultural practices of Orthodox Jewish families for childbirth and breastfeeding are discussed, with a focus on offering culturally appropriate care when the newborn is hospitalized in the neonatal intensive care unit. As breastfeeding is a critical aspect of motherhood for Orthodox Jewish women, knowing the specifics of best practices in nursing care for this unique population can help women reach their breastfeeding goals.